Management of Sex Education (Sex Education) from an Early Age for Mild Mentally Impaired Children in Extraordinary Elementary Schools (SDLB) - Hendayati, Dewi; Trisnamansyah, Sutaryat; Sauri, Sufyan; Khoeriah, Dede (CV. Inara, 2022)
Sex education equips students to have sexual behavior that is in accordance with applicable values ​​and norms and to avoid sexual harassment. Children with mental retardation who have mild intellectual disabilities have difficulty understanding the sexual symptoms they experience. This study aims to examine and explore the management of sex education for mild mentally retarded children at SLB Negeri Slawi and SLB Tebar Pesona Kasih in Brebes. The research method used is qualitative methods with collection techniques using interview, observation, and documentation studies. In this study, the theory of sex education management used refers to the “Edward Daming” theory with data assessment adjusted to the management principles of the “Daming cycle” namely PDCA: (1) planning, (2) implementation, (3) evaluation and follow-up. As for the results of the management of sex education in these two special schools, there are several research results that state the discrepancy between theory and concept due to several obstacles that become obstacles including students, parents, institutions, teachers and supporting infrastructure for sex education. Thus, it is hoped that the government can assist the SLB Negeri Slawi and SLB Tebar Pesona Kasih Brebes schools in providing sex education services that are more systematic and can be evaluated so that mild mentally retarded children are expected to have sexual behavior in accordance with values ​​and norms. there are several research results that state the discrepancy between theory and concept due to several obstacles that become barriers including students, parents, institutions, teachers and supporting infrastructure for sex education. Thus, it is hoped that the government can assist the SLB Negeri Slawi and SLB Tebar Pesona Kasih Brebes schools in providing sex education services that are more systematic and can be evaluated so that mild mentally retarded children are expected to have sexual behavior in accordance with values ​​and norms. there are several research results that state the discrepancy between theory and concept due to several obstacles that become barriers including students, parents, institutions, teachers and supporting infrastructure for sex education. Thus, it is hoped that the government can assist the SLB Negeri Slawi and SLB Tebar Pesona Kasih Brebes schools in providing sex education services that are more systematic and can be evaluated so that mild mentally retarded children are expected to have sexual behavior in accordance with values ​​and norms.